2014
DOI: 10.3906/kim-1306-28
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and X-ray powder diffraction, electrochemical, and genotoxic properties of a new azo-Schiff base and its metal complexes

Abstract: A new, substituted 2-[( E) -{[4-(benzyloxy)phenyl]imino} methyl]-4-[( E) -(4-nitrophenyl)diazenyl]phenol azoazomethine ligand (mbH) was synthesized from 2-hydroxy-5-[(4-nitrophenyl)diazenyl]benzaldehyde and 4-benzyloxyanilinehydrochloride in ethyl alcohol solution. These mononuclear Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) complexes ofthe ligand were prepared and their structures were proposed by elemental analysis, and infrared and ultraviolet-visible spectroscopy; the proton NMR spectrum of the mbH ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The magnetic measurement showed that Ni(II) complex exhibited magnetic moment of 2.92 B.M laying within the range of octahedral high spin nickel(II) complex [17]. The electronic spectra of this complex showed two spin-allowed transitions at 23148 cm -1 (432 nm) and 13003cm -1 (769 nm) corresponding to 3 A 2g → 3 T 2g and 3 A 2g → 3 T 1g , respectively [19], as shown in Fig.…”
Section: Ni(ii) Complexmentioning
confidence: 88%
See 1 more Smart Citation
“…The magnetic measurement showed that Ni(II) complex exhibited magnetic moment of 2.92 B.M laying within the range of octahedral high spin nickel(II) complex [17]. The electronic spectra of this complex showed two spin-allowed transitions at 23148 cm -1 (432 nm) and 13003cm -1 (769 nm) corresponding to 3 A 2g → 3 T 2g and 3 A 2g → 3 T 1g , respectively [19], as shown in Fig.…”
Section: Ni(ii) Complexmentioning
confidence: 88%
“…The magnetic measurement showed that Co(II) complexes exhibited magnetic moment of 4.81 B.M laying within the range of octaheadral high spin cobalt(II) complex [17]. The electronic spectrum of this complex showed an absorption band at 15384 cm -1 (650 nm); the 4 T 1g → 4 A 2g transition is characteristic of octahedral stereo chemistry [18].…”
Section: Co(ii) Complexmentioning
confidence: 99%
“…The aromatic protons of the benzene ring were allocated to multisignals within the range of 6.00–7.11 ppm. [ 34 ] At 8.55 ppm, a single signal appeared linked to the thiophenolic proton that disappeared in the complexes of FSHPd and FSHZn, which may be due to complexation of sulfur atom with the Pd(II) and Zn(II) metal ions. In all the other FSHPd and FSHZn complex signals, there is no significant change.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…We have recently published some azo-azomethines of azo-aldehydes [9,[32][33][34]. In present investigation, Ni(II), Cu(II), and Zn(II) complexes of azo chromophore group containing ONNO donor Schiff base ligand derived from ethane-1,2-diamine with 5-[(4-ethylphenyl)diazenyl]-2-hydroxybenzaldehyde were prepared and characterized by spectral methods.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are also a kind of versatile ligands in coordination chemistry [9,10]. Many Schiff base complexes show excellent catalytic activity in various reactions at high temperature and in the presence of moisture.…”
Section: Introductionmentioning
confidence: 99%